Ferrocenes as potential chemotherapeutic drugs: Synthesis, cytotoxic activity, reactive oxygen species production and micronucleus assay - Pérez, Wanda I. (Bioorg Med Chem, 2014)
Three new ferrocene complexes were synthesized with 4-(1H-pyrrol-1-yl)phenol group appended to one of the Cp ring. These are: 1,1′-4-(1H-pyrrol-1-yl)phenyl ferrocenedicarboxylate, (“Fc-(CO(2)-Ph-4-Py)(2)”), 1,4-(1H-pyrrol-1-yl)phenyl, 1′-carboxyl ferrocenecarboxylate (“Fc-(CO(2)-Ph-4-Py)CO(2)H”) and 4-(1H-pyrrol-1-yl)phenyl ferroceneacetylate (“Fc-CH(2)CO(2)-Ph-4-Py”). The new species were characterized by standard analytical methods. Cyclic voltammetry experiments showed that Fc-CH(2)CO(2)-Ph-4-Py has redox potential very similar to the Fc/Fc(+) redox couple whereas Fc-(CO(2)-Ph-4-Py)(2) and Fc-(CO(2)-Ph-4-Py)CO(2)H have redox potentials of over 400 mV higher than Fc/Fc(+) redox couple. The in vitro studies on Fc-(CO(2)-Ph-4-Py)(2) and Fc-(CO(2)-Ph-4-Py)CO(2)H revealed that these two compounds have moderate anti-proliferative activity on MCF-7 breast cancer cell line. In contrast Fc-CH(2)CO(2)-Ph-4-Py which displayed low anti-proliferative activity. In the HT-29 colon cancer cell line, the new species showed low anti-proliferaive activity. Cytokinesis-block micronucleus assay (CBMN) was performed on these ferrocenes and it was determined they induce micronucleus formation on binucleated cells and moderate genotoxic effects on the MCF-7 breast cancer cell line. There is a correlation between the IC(50) values of the ferrocenes and the amount of micronucleus formation activity on binucleated cells and the reactive oxygen species (ROS) production on MCF-7 cell line.